Desarrollo de un Plan de Marketing aplicando estrategias de publicidad y su incidencia en las ventas de la Empresa AUTOPIEZA DON RICHARD S.A. en la Ciudad de Babahoyo durante el año 2013 - Flores Poveda, Ricardo Gabriel (2014)
Presently investigation work is carried out the Strategies of Publicity and its incidence in the sales of the company GIFT RICHARD S.A, in order to analyze and to examine the current situation in which is developing the activities, so much internal as external with the purpose of being able to detect, to correct and to take advantage of the strengths, opportunities, weaknesses and threats, being able to get the objectives proposed to be competitive and reaching the success of the company. ..